THE POSITION OF “DEVON-U LUG‘OTIT TURK” IN RESEARCHING LINGVOPOETII ISSUES - Berdiyev Xusan Xolnazarovich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Particular features of history of phiylological analysis are discussed in the aspect of lingvopoetic issues in this article. The importance of studying history of lingvopoetics of “Devon-u lug‘otit turk” is proved on the basis of facts. Lisnificanceof this work (is undeslined), especialiy for lingvistics and literary studies is underlined